Factors associated with sexual dysfunction among female patients in a Nigerian ambulatory primary care setting (2020)
Background: Sexual dysfunction is a common but under-reported problem of public health importance among female adults in Nigeria. Empirical evidence on sexual dysfunction among female Nigerians is scarce. Objectives: To determine the prevalence and risk factors associated with sexual dysfunction among female patients presenting at the General Outpatient Clinic (GOPC), University College Hospital (UCH), Ibadan, Nigeria. Methods: This was a cross-sectional study of 480 married female patients who presented consecutively at the GOPC, UCH, Ibadan, Nigeria. The 28-item Sexual Function Questionnaire (SFQ-28) was used to determine sexual dysfunction. Information on their sociodemographic characteristics, obstetric and gynecological history were obtained. Bivariate and multivariate analyses were carried out and alpha was set at 0.05. Results: Point prevalence of sexual dysfunction was 80.0%. The most common sexual dysfunction was problems with sexual desire (99.4%), while the least common was problems with arousal cognition (5.8%). There was a significant association between the prevalence of sexual dysfunction and age, years of relationship, number of children alive, parity, level of education, age at coitarche and family dysfunction. Age (OR=0.893; 95% CI=0.821–0.972, p=0.008), parity (OR=3.093; 95% CI=1.174– 8.151, p=0.022), having family dysfunction (OR=2.096; 95% CI= 1.129–3.891, p=0.019) and having >10 years of formal education (OR=4.808; 95% CI= 2.604–8.928, p<0.0001) were found to be the predictors of sexual dysfunction. Conclusion: Sexual dysfunction among female married adults in our setting was high. We propose that modifiable factors such as socio-demographic and gynaecological variables should be evaluated during the consultation of female patients at first contact